Meta-analysis of the Effect of Garlic on Microbial Count in Meat Products - Ramadani, Suci Putri; Kusumaningrum, Harsi D.; Hasanah, Uswatun (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Garlic (Allium sativum L.) is a natural ingredient used for microbiological control in meat products. This study aimed to analyze the effect of garlic addition on microbial count reduction in meat products through meta-analysis. The meta-analysis was conducted using 304 extracted data points from 10 articles, analyzed with the Hedges' d method. The results showed that the addition of garlic significantly reduced microbial counts (p<0.05) in three types of meat products: raw meatballs (minced mutton), ground beef, and raw chicken meat. Among the different forms of garlic tested, freeze-dried powder, oven-dried powder, and microencapsulated essential oil were the most effective in reducing microbial counts. Garlic treatment led to a reduction in seven types of tested microbes, except for Staphylococcus aureus. The highest microbial reductions were observed for Listeria monocytogenes (-6.626 to -2.009 log₁₀ CFU/g), sulfite-reducing anaerobes (-4.521 to -2.193 log₁₀ CFU/g), and Escherichia coli (-2.771 to -1.225 log₁₀ CFU/g).